A cadeia de produção do mel no Rio Grande do Sul: a organização e a governança nas transações dos apicultores associados à Apismar - Coelho Junior, João Carlos (2011)
This study aims to determine the organization and governance in the transactions of APISMAR beekeepers and describe the honey production chain in Rio Grande do Sul. It is used as a theoretical framework the concept of agroindustrial production chain, the structure-conduct-performance paradigm (SCP), and the theory of transaction cost economics (TCE). The research method used is the descriptive and exploratory with primary data (structured questionnaires applied to the beekeepers and interview conducted with the president of APISMAR) and secundary data. The results showed that the Brazilian honey production has increased in the last few years, and that the state of Rio Grande do Sul is the main producer. The Northern mesaregion, the Central Campanha and the municipality of Santana do Livramento represent 35% of the honey production in the state. The beeking activity in the state is developed by 27 thousand beekeepers, and 50% of the production is exported, mainly to the US, which is the largest honey importer. With regards to APISMAR members, it was found that the production is predominantly concentrated on a small property (1 - 5 ha), which has been involved in this activity for a long time (over 10 years) using hand-operated technology and native flora. Moreover, regarding the structure, the producers have not been diversifying the production nor the product and have considered as their main barrier to the entrance, the difficulties in sales. They have practiced price fixing igual to the average market value and worked on cost reduction. The number of honey producers is concentrated in the extract of 1 to 50 hives and the average honey productivity is 27 kg/hive/year. With regards to the governance in the beekeepers transactions, it was found the prevalence of via market transaction mainly due to the low uncertainty and asset specificity.